Time-slot allocation algorithm for LEO satellite beam hopping based on non-stationary MAB - Min LIN; Pengcheng KAN; Bai ZHAO; Ming CHENG; Lyuxi YANG (Tongxin xuebao)
Aiming at the problem of inadequate adaptation to dynamic changes in cell services in the resource allocation algorithm for hopping beams in low earth orbit (LEO) satellite systems, a time-slot allocation algorithm for LEO satellite beam hopping based on a non-stationary multi-armed bandit (MAB) was proposed.Firstly, the joint optimization problem of slot allocation and beam grading matching was established, with the minimization of the system’s second-order differential capacity as the optimization objective.Secondly, due to the non-convexity and difficulty in direct solution of this problem, a beam grading combination scheme generation algorithm was proposed based on the concept of effective cells and effective critical cells, which generated all possible beam grading combination schemes.Next, a dynamic slot allocation scheme based on the non-stationary MAB model was proposed, and joint optimization of slot allocation and beam grading matching was completed under the optimal beam grading combination scheme.Finally, the computer simulation results show that the average redundancy of the proposed algorithm is less than 20% in the case of multiple cell service distributions.In addition, compared with other schemes, the proposed algorithm can control the average beam revisit time to about 300 ms while maintaining high system throughput.